Hematological parameters of COVID-19 patients at Jakarta Pondok Kopi Islamic Hospital - Sanjaya, Arief Indra; Martalena, Dewi; Maki, Naoki (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2024)
Background: The 2019 Corona Virus Disease (Covid-19) has become a pandemic. As of 15 January 2021, 223 countries have been infected, with a total number of 92,262,621 confirmed cases, and 1,995,037 deaths. In Indonesia, as of the same date, there were 896,642 confirmed cases and 25,767 deaths.1 Diagnosis of COVID-19 is based on real-time reverse transcriptase-polymerase chain reaction (RT-PCR) results on oropharyngeal/nasopharyngeal swab samples.2 A basic hematological examination is also conducted on patients with suspected COVID-19. The results of baseline hematological examinations are thought to be a predictor of the patient being infected with COVID-19 before the RT-PCR results are released. The purpose of this study is to identify the hematological parameters of COVID-19 patients at Pondok Kopi Islamic Hospital in Jakarta (RSIJ PK) in order to provide an overview of the hematological parameters that can be used to predict the possibility of a patient being infected with COVID-19. Methods: The study adopted a cross-sectional approach, using the database on COVID-19 patients at Pondok Kopi Islamic Hospital. Data variables were categorized and described by frequency and percentage. Statistical analysis was conducted using the likelihood ratio test and SPSS (statistical package for the social sciences) version 26. Results: The number of research respondents was 250, with 142 males (56.8%). The majority of participants were between the ages of 40 and 59, at 127 (50.8%). Most patients exhibited a moderate level of clinical severity, at 215 (86%). The three most common comorbidities were hypertension in 82 patients (32.8%), diabetes in 68 patients (27.2%), and chronic kidney disease in 27 patients (10.8%). The dominant hematological parameters were normal blood leukocytes in 157 patients (62.8%), increased Neutrophil/Lymphocyte Ratio (NLR) (>3.13) in 148 patients (59.2%), low Absolute Lymphocyte Count (ALC) (<1500/µL) in 133 patients (53.2%), increased C-Reactive Proteins (CRP) (>10 mg/L) in 171 patients (68.4%), and increased d-dimer (>0.5 µg/mL) in 148 patients (59.2%). There was a significant correlation between age (p 0.028), comorbid hypertension (p 0.002), comorbid diabetes (p 0.011), leukocyte levels (p 0.045), and ALC levels (p 0.025), and the severity of the COVID-19 disease. Conclusions: The majority of COVID-19 patients had normal blood leukocyte levels, increased NLR, low ALC, and increased CRP and d-dimer.